Religion and Science: Analysing Medical Fatwas of the Majelis Ulama Indonesia (2010–2021) - Sodiqin, Ali (Institut Agama Islam Negeri (IAIN) Pontianak, 2025)
The advancement of knowledge, particularly in the medical field, often surpasses established religious norms, giving rise to new legal challenges. This presents a significant issue for Islamic scholars and modern institutions such as Majelis Ulama Indonesia (the Indonesian Ulema Council, MUI). This article examines the dialectical relationship between revelation (naṣṣ) and science in the medical fatwas issued by the MUI, focusing on how Islamic scholars construct legal arguments by integrating the Qur’an and Hadith with scientific findings to advance scientific ijtihād (Islamic legal reasoning). Adopting a qualitative, library-based methodology, the study meticulously analyses 20 medical fatwas issued by the MUI between 2010 and 2021. Using a functional interpretive paradigm that incorporates revelation, reason, and reality as foundational elements of fatwa formulation, the article finds that the MUI engages in a dialogical process between revelation and science in its medical fatwas. The dialectic between naṣṣ and scientific discoveries reveals two models of integration: deductive-falsification and inductive-verification. The deductive-falsification model appears in fatwas offering guidance for specific actions, while the inductive-verification model is applied in determining the legal status of scientific products. These integration models demonstrate that the MUI positions naṣṣ as the independent variable and scientific findings as the dependent variable in the development of scientific ijtihād. This approach emphasises the decisive role of revelation in determining the acceptability of scientific advancements as the foundation for legal rulings. [Kemajuan ilmu pengetahuan, khususnya di bidang medis, sering kali melampaui norma-norma agama yang mapan, sehingga menimbulkan berbagai persoalan hukum baru. Hal ini menjadi tantangan bagi para ulama dan lembaga Islam modern seperti Majelis Ulama Indonesia (MUI). Artikel ini mengeksplorasi hubungan dialektika antara wahyu (naṣṣ) dan sains dalam fatwa-fatwa medis yang dikeluarkan MUI, serta bagaimana para ulama membangun dalil-dalil hukum dengan mengintegrasikan Alquran dan hadis dengan temuan-temuan ilmiah dalam pengembangan ijtihad ilmiah. Dengan mengadopsi metode kualitatif berbasis kepustakaan, penelitian ini menganalisis secara cermat isi dari 20 fatwa medis yang dikeluarkan MUI sejak tahun 2010 hingga 2021. Dengan menggunakan paradigma interpretatif fungsional yang mempertimbangkan wahyu, akal, dan realitas sebagai dasar pertimbangan fatwa, artikel ini menemukan bahwa MUI telah melakukan dialog antara wahyu dan sains dalam memproduksi fatwa-fatwa medisnya. Dialektika antara naṣṣ dan temuan-temuan ilmiah dalam fatwa-fatwa tersebut menunjukkan adanya dua model integrasi: deduktif-falsifikasi dan induktif-verifikatif. Model deduktif-falsifikasi ditemukan dalam fatwa-fatwa yang memberikan pedoman bagi umat Islam untuk mengamalkan tindakan-tindakan tertentu, sedangkan model induktif-verifikatif muncul dalam fatwa-fatwa yang menetapkan status hukum (halal atau haram) bagi produk-produk sains. Kedua model integrasi ini menunjukkan bahwa MUI telah memosisikan naṣṣ sebagai variabel independen dan temuan-temuan ilmiah sebagai variabel dependen dalam pengembangan ijtihad ilmiah. Temuan-temuan ini menempatkan wahyu sebagai faktor penentu diterima atau tidaknya suatu produk ilmiah sebagai dasar putusan hukum.]